FUNDC1 collaborates with PINK1 in regulating mitochondrial Fission and compensating for PINK1 deficiency. - Xu, J.; Deng, Z.; Shang, S.; Wang, C.; Han, H. (Biochemical and Biophysical Research Communications, 2023)
Parkinson's disease is presently thought to have its molecular roots in the alteration of PINK1-mediated mitophagy and mitochondrial dynamics. Finding new suppressors of the pathway is essential for developing cutting-edge treatment approaches. Our study shows that FUNDC1 suppressed PINK1 mutant phenotypes in Drosophila. The restoration of PINK1-deficient phenotypes through FUNDC1 is not reliant on its LC3-binding motif Y (18)L (21) or autophagy-related pathway. Moreover, the absence of Drp1 affects the phenotypic restoration of PINK1 mediated by FUNDC1 in flies. In summary, our findings have unveiled a fresh mechanism through which FUNDC1 compensates for the loss of PINK1, operating independently of autophagy but exerting its influence via interaction with Drp1.